Radiation Doses and Risks in Breast Screening. Issue 3 (24th April 2020) - Hendrick, R Edward
Abstract: This article describes radiation doses and cancer risks of digital breast imaging technologies used for breast cancer detection. These include digital mammography (DM), digital breast tomosynthesis (DBT), and newer technologies such as contrast-enhanced digital or spectral mammography (CEM), whole-breast computed tomography, breast-specific gamma imaging (BSGI), molecular breast imaging (MBI), and positron emission mammography (PEM). This article describes the basis for radiation risk estimates, compares radiation doses and risks, and provides benefit-to-radiation-risk ratios for different breast imaging modalities that use ionizing radiation. Current x-ray–based screening modalities such as DM and DBT have small to negligible risks of causing radiation-induced cancers in women of normal screening age. Possible new screening modalities such as CEM have similar small cancer risks. Potential screening modalities that involve radionuclide injection such as BSGI, MBI, and PEM have significantly higher cancer risks unless efficient detection systems and reduced administered doses are used. Benefit-to-radiation-risk estimates are highly favorable for screening with DM and other modalities having comparable (or higher) cancer detection rates and comparably low radiation doses.